The Significance of existing Non-Existent Absent characters in Nineteen Eighty Four by George Orwell and Waiting for Godot' by Samual Beckett - Kruti J.Desai, (AG Volumes, 2022)
In the work of Samuel Beckett, "Waiting for Godot," the existential mode of thought is brought to light in this exploration study (1949). One of the most well-known examples of the Theater of the Absurd is the play waiting for Godot. The 'Sisyphean' nature of the human condition lies at the heart of it. However, the absurdity lies in the existentialist belief that existence has no purpose, and despite the fact that the choices we make are meaningless in the grand scheme of things, they nonetheless shape who we are at the end of the day. Everything is repeating itself and becoming more meaningless. Through “Nineteen Eighty Four” George Orwell takes his readers into a bleak future where Big Brother watches their every move. As most of it is written in the past tense, 1984 is not your usual dystopian novel that you may read in modern literature. Existence is as pointless as a balloon full of air. All of these problems are aftereffects of the catastrophe that is global war. The presence of both God and the person was being discussed. Every journalist who subscribed to the existentialist school of thought advocated the idea that an individual should acknowledge his or her own uniqueness and give up searching for a rescuer or a divine power that might solve the problems faced by other people. This analysis study used literary evidence from "Waiting for Godot" and “Nineteen Eighty Four” to analyse the absurdity in Beckett's and George Orwell’s work and show how the writer successfully introduced topics for discussion regarding human depravity.